Synthesis and optimization of chitosan nanoparticles loaded with l-ascorbic acid and thymoquinone - Othman, Nurhanisah; Masarudin, Mas Jaffri; Cha, Yee Kuen; Dasuan, Nurul Azira; Abdullah, Luqman Chuah; Md. Jamil, Siti Nurul Ain (MDPI, 2018)
The combination of compounds with different classes (hydrophobic and hydrophilic characters) in single chitosan carrier is a challenge due to the hydrophilicity of chitosan. Utilization of l-ascorbic acid (LAA) and thymoquinone (TQ) compounds as effective antioxidants is marred by poor bioavailability and uptake. Nanoparticles (NPs) solved the problem by functioning as a carrier for them because they have high surface areas for more efficient delivery and uptake by cells. This research, therefore, synthesized chitosan NPs (CNPs) containing LAA and TQ, CNP-LAA-TQ via ionic gelation routes as the preparation is non-toxic. They were characterized using electron microscopy, zetasizer, UV–VIS spectrophotometry, and infrared spectroscopy. The optimum CNP-LAA-TQ size produced was 141.5 ± 7.8 nm, with a polydispersity index (PDI) of 0.207 ± 0.013. The encapsulation efficiency of CNP-LAA-TQ was 22.8 ± 3.2% for LAA and 35.6 ± 3.6% for TQ. Combined hydrophilic LAA and hydrophobic TQ proved that a myriad of highly efficacious compounds with poor systemic uptake could be encapsulated together in NP systems to increase their pharmaceutical efficiency, indirectly contributing to the advancement of medical and pharmaceutical sectors.